Modification of Casava Starch Properties by Spontanesous Fermentation - Neti Yuliana; Ica Dwi Kusuma Wardani; Dewi Sartika; Siti Nurdjanah (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2023)
The impact of spontaneous fermentation on the physical and chemical characteristics of fluidized cassava starch treated in a sedimentation tank were examined. Tapioka, aci puter, and elot are three types of casava starch products that were made from starch slurry collected at various periods of spontaneous fermentation. By different spontaneous fermentation time, the appearance of granules was significantly changed. Besides, there was diffrent response color to iodine test indicating a different amylopectin chain-length distribution pattern. Among them, there were significant differences in moisture content, swelling power, water absorption ratio, gel formation ability and pH value. These studies showed that spontaneous fermentation might be used to modify casava starch products.